Memory and perception in autobiographical interviews: an episodic simulation that adapts in real-time to the context - Guerrero Velázquez, Carlos Alberto (Estudios de Filosofía, 2021)
Perception and memory are usually thought to be two independent faculties, where the former is believed to only have an influence on the latter at encoding. In autobiographical interviews of oral history and historical memory, interviewees select, adapt, and complete their memories to create different versions. This paper argues that this process is a consequence of the simulative nature of episodic memory and the interviewees’ use of perceptual information to generate and adapt their memories to an autobiographical discourse with the goal of satisfying a communicative purpose. To illustrate this, three contextual factors (communicative aim, language of communication, and emotional interaction) that influence the construction of a memory in an autobiographical interview are analyzed, showing that, in this type of recall, memory and perception simultaneously contribute to constructing episodic simulations of events, which adapt in real-time to the context in which recall happens.